Perlindungan Hak Anak dalam Perceraian: Perspektif Kompilasi Hukum Islam dan Implementasinya di Pengadilan Agama Purworejo Nomor Perkara 122/Pdt.G./2022/PA.Pwr - Widyastuti, Anggita; M. Mustahal; Najih Abqori (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The rising divorce rate in Indonesia has serious impacts on children, who are the most vulnerable parties, both psychologically and materially. Legal protection for children's rights after divorce is regulated in Law Number 35 of 2014 on Child Protection and the Compilation of Islamic Law (KHI), which upholds the principle of The Best Interest of the Child. Articles 105 and 156 of the KHI specifically govern child custody and financial support. However, the implementation of these provisions continues to face various challenges in practice. This study aims to analyze the protection of children's rights in divorce cases from the perspective of the KHI and to evaluate its implementation in the Religious Court of Purworejo. The research uses a juridical-empirical method with a qualitative approach, including document studies and interviews with judges and related parties.The findings indicate that, normatively, the KHI provides a strong legal foundation for child protection. However, its application still encounters obstacles such as low legal awareness, limited evidence, and economic constraints, particularly in the enforcement of child support rulings.This study recommends strengthening legal education for the public and enhancing the role of the court in ensuring fair and sustainable implementation of children’s rights after divorce.